COMENSALIDADE E ASCESE: CONFLITOS DE PROJETOS MESSIÂNICOS A PARTIR DE LC 7,31-35 - Orti, Luiz Vitório (2007)
To eat or not to eat? To drink or not to drink? What, with whom, when, where and how? These are questions which accompanied the humanity s history, and they also were very significant in the Mediterranean nations cultural context since the first century after Christ. Tell me what you eat and I tell you who you are , added to Tell me with whom you eat , are sayings that summarize the whole cultural and symbolical content (social, economical, political and religious ones) linked to feeding and its sharing. Possessing the devil , while accusation against John the Baptist; Look! A glutton and drunkard, friend of tax gatherers and sinners as the blemish attributed to Jesus: the Jesus´ table fellowship, in divergence with the Baptist´s ascesis and with that generation s patterns, became evident a conflict between distinct social and religious conceptions. For Jesus and his followers, itinerant thaumaturgists, the binomials miracle/ table and healing / meal, are the propitious places to make happen the gift mechanism: giving, receiving and retributing.(AU)